2014
DOI: 10.1016/j.ijheatmasstransfer.2014.04.065
|View full text |Cite
|
Sign up to set email alerts
|

Modeling for non isothermal cavitation using 4-equation models

Abstract: International audienceA compressible, two-phase, one-fluid solver has been developed to investigate the behaviour of cavitation models including thermodynamic effects. The code is composed by three conservation laws for mixture variables (mass, momentum and total energy) and a supplementary transport equation for the void ratio. Two formulations for the mass transfer between phases are studied. Numerical simulations are firstly performed on rarefaction cavitating problems in which the working fluid is hot wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…The cavitation solvers solve the conservative form of the Navier-Stokes equation but use different approaches in handling the state equation and the two-phase modelling. The first solver is based on a barotropic equation of state (denoted herein as BES -Barotropic Equation-of-state based Solver), which directly couples the density to the pressure [23,24]. The minimal speed of sound of the mixture is used as a fitting parameter for the model.…”
Section: Computational Modelling and Setup 21 Numerical Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cavitation solvers solve the conservative form of the Navier-Stokes equation but use different approaches in handling the state equation and the two-phase modelling. The first solver is based on a barotropic equation of state (denoted herein as BES -Barotropic Equation-of-state based Solver), which directly couples the density to the pressure [23,24]. The minimal speed of sound of the mixture is used as a fitting parameter for the model.…”
Section: Computational Modelling and Setup 21 Numerical Toolsmentioning
confidence: 99%
“…Bluff body cavitationHemispherical headform [29] Inducer blade passage cavitation -2D Venturi [24] Attached leading edge cavitation -Hydrofoil [30] Rotational flow cavitation -Ship Propeller (3D) The first case deals with the bluff body cavitation occurring at the inducer boss. This domain is simplified to an axisymmetric hemispherical headform.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Recently, a new four-equation cavitation model with consideration of thermodynamic effects has been presented by Goncalves et al [30][31][32]. Their results showed that the new model performed well for sheet cavitation cases.…”
Section: State Of the Artmentioning
confidence: 99%
“…RANS turbulence models have been used to simulate various industrial fluid machines for years because of their good performance in giving acceptable simulation results within a reasonable computational time. For cavitating flow simulations, recent CFD studies showed that these turbulence models would need some modifications in the turbulent eddy viscosity [31,33,34]. There are several different RANS turbulence models for different utilities.…”
Section: State Of the Artmentioning
confidence: 99%
“…The vapour pressure is assumed to vary linearly with the temperature though the parameter dP vap /dT . Validations have shown the ability of such models to correctly simulate cavitation pockets in both water and freon R-114 (Goncalves 2013, Goncalves & Charriere 2014, Goncalves 2014, Charriere et al 2015, Goncalves & Zeidan 2015. In order to investigate thermal effects in LH 2 cryogenic cavitating flows, one-dimensional cavitation tube problems are proposed.…”
Section: Introductionmentioning
confidence: 99%